“NGELEBENGANG” TRADISI PEMBUATAN GULA AREN DESA PEDAWA DALAM FOTOGRAFI STORY - Gusti Putu Richie Efendi Pranata; Cokorda Istri Puspawati Nindhia; Farhan Adityasmara (Lp2mpp Isi Denpasar - Ps. Fotografi, 2021)
Palm sugar is sugar made from sap or palm tree juice. Most people prefer palm sugar because it is considered more fragrant, tasty and clean. Pedawa Village is a village that still maintains the tradition of making palm sugar known as